PENGARUH STRATEGI PEMASARAN TERHADAP PENINGKATAN JUMLAH NASABAH DALAM PRODUK PEMBIAYAAN BANK SYARIAH - Kharisma, Kharisma; Ayu Ciptaningsih, Sri; Cigmawanti Septianingsih, Cindy; Hanifah, Nani (AT TARIIZ : Jurnal Ekonomi dan Bisnis Islam, 2023)
This study explores the effect of marketing strategies on increasing the number of customers in Islamic bank financing products. We analyze how marketing strategies, including market segmentation, ethical approach, use of technology, and regulatory compliance, affect the ability of Islamic banks to attract new customers and promote their growth. This research uses the literature review method as the main approach. The literature review method is a way to collect, evaluate, and synthesize information from various literature sources relevant to the research topic. In the context of this research, the literature review method is used to identify and analyze previous studies, theories, and concepts related to the effect of marketing strategies on increasing the number of customers in Islamic bank financing products and data analysis, this research identifies that effective marketing strategies can play an important role in expanding the market share of Islamic banks and influencing their growth. Overall, marketing strategies play a crucial role in the growth of Islamic banks and the increase in the number of customers in financing products. Through a targeted and effective approach, banks can reach a wider target market, make customers aware of the benefits of Islamic financing products, and emphasize important ethical values. An effective marketing strategy not only influences revenue growth from financing products, but also shapes the bank's reputation and strengthens relationships with customers.The results of this study can provide valuable insights for Islamic banks and other stakeholders in the Islamic banking industry.